Orang-orang Melayu dalam Sistem Pemerintahan Kerajaan Gowa - Usman Nomay (Rayhan Intermedia, 2017)
This article contains the results of research on the position and role of the Malay People in the Kingdom of Gowa. The presence of Malays and then occupy an important position in this area is inseparable from the application of open-door politics of the Kingdom of Gowa-Tallo. Thus, Malay traders were accepted and made trade relations with local residents and other ethnic immigrant. The long journey of social relationships that exist between elements of society then unite them in various forms of relationships. The existence of Malay in Makassar, then brought significant changes, marked their role in various important positions such as: head of port (syahbandar), clerk on the kingdom of Gowa and also appeared as an announcer of Islamic teachings. Experts such as blacksmiths, goldsmiths, home builders, construction experts, chopsticks makers, metal-making artisans, masons, masons, and pemental ropers are part of the Malay-Makassar relationship.